Providing Confidentiality, Integrity and Atomicity for data stored in the cloud storage - Bansal, Akanksha; Agrawal, Arun (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a kinds of computing that depend on distribution computing resources before having local servers or own devices to knob applications. Cloud computing is equivalent to grid computing, In the cloud is a kind of computing where vacant handing out rounds of the entire computers in a network are harnesses to solved the concerns also focused for some stand-alone mechanism. Cloud computing security mentions to the group of processes, procedures and standards designed to deliver information security guarantee in a cloud environment. Cloud computing security comprises both logical and physical security concerns across all the diverse various models of software platform, infrastructure and software. It also defines how these services are delivered (public, private or hybrid delivery model).